40-year reform of farmland institution in China: target, effort and the future. Issue 1 (5th February 2018) - Luo, Bilang
Abstract : Purpose: Based on the brief historical review, the purpose of this paper is to expound the target and bottom line for the farmland institutional reform of in China, analyze the "Chinese scenes" and historical heritage of farmland institutional arrangement, evaluate the policies and their effects over the last four decades and outline the keynotes and possible direction of the future reform. Design/methodology/approach: The paper builds the analytical clue of "institutional target – institutional heritage – policy effort – realistic dilemma – future direction" and review and forecast the Chinese farmland institutional reform. Findings: The farmland institution is an important issue with Chinese characteristics. Over the last four decades, the farmland institutional reform in China has focused on "stabilizing the land property rights" and "promote the farmland transfer." As the study indicates, the promotion of farmland transfer has not effectively improved the scale economy of agriculture and stabilizing land property rights by titling may restrain the development of farmland transfer market because farmland transfer is of special market logic. Originality/value: It depends on the revitalization of farmland management rights to resolve the transaction constraint of personal property and its endowment effect in farmland transfer. And, classifying the land management property to involve farmers into the economy of division can be reference for the reform of traditional agriculture worldwide.